HUBUNGAN STRES DENGAN SIKLUS MENSTRUASI PADA MAHASISWA TINGKAT AKHIR DI INSTITUT AGAMA ISLAM NEGERI PONTIANAK - Solehah, Imroatus; Hikmawati, Nova; Ekasari, Tutik (Forind Press, 2025)
The ideal menstrual cycle is regular every month with a range of 24-35 days for each menstrual period. Many factors can influence the menstrual cycle, and one of them is stress. Stress involves the neuroendocrine system, which can affect the menstrual pattern. The aim of this research is to determine the relation between stress level and menstrual cycle among senior female students at the State Islamic Institute of Pontianak. This research is a correlation study with a cross-sectional design using accidental sampling technique, involving 62 respondents who met the inclusion and exclusion criteria. Based on the Chi-Square test results, P Value of 0.189 was obtained, which means P Value is bigger than 0.05. Therefore, it can be concluded there is no significant relation between stress level and menstrual cycle among senior female students at the State Islamic Institute of Pontianak. The result of this study indicate that there is no significant relation between stress level and menstrual cycle among senior female students at the State Islamic Institute of Pontianak. Therefore, it is recommended for students to conduct self-evaluation and increase their knowledge about menstruation and stress to avoid stress and irregular menstrual cycle.